1999
DOI: 10.1111/j.1745-4557.1999.tb00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ground Pork and Pork Sausage Containing Different Forms of Apple Products

Abstract: Fat contents of ground pork were altered by reducing the amounts of fat trim incorporated and by the inclusion of diferent apple products dfi-esh, rehydrated, and sauce). Panelists could discriminate between ground pork containing 15% or 30% fat (without apples) and between groundpork with 0% or 15% apple (25% fat) but not between formulations with 15% or 25% fat and 10% apple (p<0.05). Incorporation of apple products (15% of total formulation weight) into reduced-fat pork sausage containing 15% fat yielded fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…During preparation of a sausage, some sugars should be added into the mixed product, which could improve both the texture and the taste of sausage (Edwards et al 1999). So it is important to analyze the physical changes of such MBG/starch mixed gels with added sugars.…”
mentioning
confidence: 99%
“…During preparation of a sausage, some sugars should be added into the mixed product, which could improve both the texture and the taste of sausage (Edwards et al 1999). So it is important to analyze the physical changes of such MBG/starch mixed gels with added sugars.…”
mentioning
confidence: 99%
“…A sensory panel found that pork sausage with 15°Io fat could be used if water was added to replace the rest of the fat (control is 35% fat content) (Ahmed et al, 1990). Edwards et al (1999) used different forms of apple products to reduce the amount of fat in pork sausage. They found that there were no significant differences in consumer acceptance between 15% fat sausage with the apple products and 30% fat sausage without the apple products.…”
Section: Reduction In Fatmentioning
confidence: 99%